2023
DOI: 10.1039/d2cc06495b
|View full text |Cite
|
Sign up to set email alerts
|

Versatile nanodiamond-based tools for therapeutics and bioimaging

Abstract: Nanodiamonds (NDs) are a remarkable class of carbon-based nanoparticles in nanomedicine which have recently become a hot topic of research due to their unique features including functionalization versatility, tunable opto-magnetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 195 publications
0
7
0
Order By: Relevance
“…The use of microorganisms or plant extracts to synthesize nanoparticles allows for obtaining nanoparticles with high biocompatibility. Recent research showed that nanoparticles synthesized by such green synthesis methods have surfaces coated with proteins, fibers, and carbohydrates that provide them greater biocompatibility than those of the same size and shape but synthesized using chemical methods [ 38 , 39 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…The use of microorganisms or plant extracts to synthesize nanoparticles allows for obtaining nanoparticles with high biocompatibility. Recent research showed that nanoparticles synthesized by such green synthesis methods have surfaces coated with proteins, fibers, and carbohydrates that provide them greater biocompatibility than those of the same size and shape but synthesized using chemical methods [ 38 , 39 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…20 Surface chemical modication of NDs has been extensively investigated, primarily to address colloidal stability, biocompatibility, and interaction with surrounding tissues. [15][16][17] These properties, combined with high photostability, lead to wide applications of NDs in biomedicine, [11][12][13][14][15][16][17] including drug delivery and long-term cell tracking. 21 For example, carboxyl groups on the surface of NDs were modied with poly(ethylene glycol) (PEG) and subsequent physisorption of doxorubicin (DOX), achieving higher drug loading and increased drug efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanodiamonds (NDs) have emerged as excellent candidates for bioimaging, biosensing and drug delivery. 11–17 This can be attributed to the excellent properties offered by NDs such as high photostability (nearly quantitative yield), excellent biocompatibility, high chemical stability and great thermal conductivity. 11–13…”
Section: Introductionmentioning
confidence: 99%
“…Nanodiamonds are another/important class of biomaterial primarily made of interlinked tetrahedral of sp 3 hybridized carbon. Nanodiamonds have various applications in electronic sensor, functional coating, bioimaging, drug delivery, and tissue engineering . Nanodiamonds are usually synthesized by detonation, high pressure high temperature, and chemical vapor deposition methods …”
Section: Introductionmentioning
confidence: 99%